Obtenção de hidrolisado proteico de sementes de quiabo Abelmoschus esculentus (L.) Moench e sua capacidade antioxidante - Nascimento, Edilza Silva do (2015)
The reactive oxygen species (ROS) are generated through reactions physiologically normal in the human organism during the respiratory process and perform various functions such as signage and providing defense against infections. However, in excessive amounts the ROS cause cellular damage and are involved in the initiation or progression of degenerative chronic diseases. In contrast, the antioxidant agents play a vital role for reduce the processes oxidative in the organism. Among them are hydrolyzed peptides from protein sources and, that demonstrate antioxidant activity. However, it is necessary the hydrolytic process for release of small fragments of amino peptide with the capacity to reduce the ROS. However, the conditions of hydrolysis employed such as type of enzyme, enzyme concentration, pH, time and temperature can influence the formation of peptides with antioxidant properties. Thus, this study aimed to obtain hydrolyzed from okra seed proteins using Alcalase® hydrolytic enzyme in different conditions and evaluate the antioxidant capacity of the hydrolysates produced. Using a Central Composite Rotatable Design (CCRD), was evaluated the influence of independent variables: enzyme concentration (EC) and hydrolysis time (T), on the dependent variables: degree of hydrolysis (DH), protein recovery efficiency (PRE), total antioxidant capacity (TAC) and scavenging of radicals radicais 2.2’-azinobis-(3-ethylbenzothiazoline)-6-sulfonic acid (ABTS) e 2.2-diphenyl-1-picrilidrazil (DPPH). The results showed that the increase in EC and T influenced positively on DH and TAC and only increased T influenced on the PRE, the ability of eliminating radical ABTS and DPPH were not influenced by the independent variables. It was verified that the increased TAC is directly into proportional to the increase in DH. The electrophoretic profile revealed that okra seed protein concentrate (OSPC), presents protein bands with relative masses above 38 kDa and less than 8.5 kDa. It was also found, the efficiency of the process of hydrolysis by Alcalase®, evidenced by the disappearance of most of the protein bands and the appearance of peptides of molecular mass < 3.5 kDa in hydrolysates with a higher DH. The OSPC showed lower TAC and ability of the ABTS and DPPH radical scavenger in comparison to the hydrolysates obtained. The best operating conditions of the independent variables (EC and T) obtained in the optimization study, using the methodology CCRD was possible to obtain a hydrolyzate considered optimal, the enzyme concentration was 2% and time of hydrolysis of 300 min, in this condition the hydrolyzed resulted in increased DH (19.32%), TAC (51.54%) and significant results for DPPH (52.60%) and ABTS (73.04%). The hydrolyzed great presented a considerable content of amino acids with ability to donate protons and electrons, especially acids (32.90 g/100 g of protein), hydrophobic (38.58 g/100 g of protein) and aromatic (9.43 g/100 g of protein). The results show that the protein hydrolyzate of okra seed emerges as a promising bioactive compound, with antioxid capacity. However, other studies are needed to assess the effects that the hydrolysate can produce in vivo, in order to verify the effectiveness of antioxidant activity in the human organism.